2022
DOI: 10.1039/d2cy00311b
|View full text |Cite
|
Sign up to set email alerts
|

Observation of surface species in plasma-catalytic dry reforming of methane in a novel atmospheric pressure dielectric barrier dischargein situIR cell

Abstract: We developed a novel in-situ (i.e. inside plasma and during operation) IR dielectric barrier discharge cell allowing investigation of plasma catalysis in transmission mode, atmospheric pressure, flow conditions (WHSV ~...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Transmission IR can be used and has some advantages, such as easier quantitative studies, less temperature dependence, no grain size dependence and smaller temperature gradients in the catalyst material [123]. Transmission IR cells have been developed for a low-pressure glow discharge plasma [124] and, more recently, also for a DBD at atmospheric pressure under continuous flow [125,126]. Ideally, if in-situ IR cells can be coupled to gas chromatography (GC) or mass spectrometry (MS) at the gas outlet, this will enable operando studies, i.e.…”
Section: How To Overcome the Challenges And Create New Opportunitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Transmission IR can be used and has some advantages, such as easier quantitative studies, less temperature dependence, no grain size dependence and smaller temperature gradients in the catalyst material [123]. Transmission IR cells have been developed for a low-pressure glow discharge plasma [124] and, more recently, also for a DBD at atmospheric pressure under continuous flow [125,126]. Ideally, if in-situ IR cells can be coupled to gas chromatography (GC) or mass spectrometry (MS) at the gas outlet, this will enable operando studies, i.e.…”
Section: How To Overcome the Challenges And Create New Opportunitiesmentioning
confidence: 99%
“…measuring the plasma-catalytic performance together with the surface characterisation [125,127]. However, operation under plasma conditions requires that the electrodes of the plasma reactor are spatially separated from any metallic parts of the spectrometer, which yields large dead volumes in most IR cells so that measured conversions are typically low [126]. This makes in-situ operando plasma catalysis studies not yet very straightforward.…”
Section: How To Overcome the Challenges And Create New Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, X-rays-based methods are also gaining interest for in-situ structural analysis of catalysts because of the brightness of synchrotron radiation (e.g., [130]). Finally, in-situ measurement of the catalyst surface temperature in a DBD plasma provides valuable insights, although such measurements are also quite challenging [122,126,130].…”
Section: How To Overcome the Challenges And Create New Opportunitiesmentioning
confidence: 99%
“…In all our experiments, the gas temperature at the outlet of the reactor was about 20-25 ℃, and the temperature of the external electrode was about 50 ℃. Also, Van Turnhout et al recently presented a novel method to determine the temperature of the catalyst surface, and revealed that the plasma-induced temperature rise in a DBD reactor is limited (≤ 150 ℃) [51]. It might always be possible that the temperature in the reactor is higher at some places (local hot spots) and dependent on the type of packing material and operating conditions; however, since thermal dry reforming hardly takes place below 300 ℃ [38], we can consider that the conversion of CH4 and CO2 in our reactor is mainly due to the plasma reaction.…”
Section: Catalyst Performance Evaluationmentioning
confidence: 99%